Optimizing Student Character Strengthening Through Creative Week Activities at MI Al Hidayah Karanggintung - Ummun Naja, Farhah; Mayasari, Novi (Literacy: Journal of Education and Social Science, 2025)
This study aims to describe the implementation of creative character cultivation in grade IV students through Creative Week activities at MI Al-Hidayah Karanggintung, Banyumas Regency. This study uses a descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. The results of the study show that the implementation of creative character cultivation is carried out through three stages, namely planning, implementation, and evaluation. The planning stage includes the preparation of thematic activities such as Market Day, Cooking Day, Fun Day, and Cleaning Day which are designed to provide space for students to develop their creativity. In the implementation stage, students are given the freedom to express their ideas according to their interests and talents, with support from the teacher as a facilitator. Meanwhile, at the evaluation stage, teachers and students together reflect on activities for future improvement. This research has succeeded in revealing that Creative Week activities can effectively be a medium in instilling creative character in students. This can be seen from the students' enthusiasm, increased confidence, and students' ability to produce original works. In addition, this activity also encourages the creation of a fun and meaningful learning climate. Therefore, this study recommends that this kind of activity be developed in a sustainable manner by involving all elements of the school and parents in its implementation.